Lightweighting a fire-truck frame: CAD–FEA benchmarking of SS304, IS 2062, and Al 7075-T6 for stiffness, safety, mass, and cost - Ranjan, Akhilesh; Wadia, Viraz; Khatri, Narendra; Patro, K Abhimanyu Kumar; Singh, Mandeep; Pandey, Vineet; Pokhriyal, Sumit (Edelweiss Applied Science and Technology, 2025)
Reducing structural mass without compromising safety is central to improving the efficiency and operational capability of heavy emergency vehicles. This study evaluates three widely deployable materials, Stainless Steel (SS 304), Mild Steel (IS 2062), and Aluminum 7075-T6, for a fire-truck superstructure frame using a controlled CAD–FEA protocol. A full-scale ladder-frame was modeled in SolidWorks and analyzed in ANSYS (static structural) under identical boundary conditions representative of service loads (fixed runners on chassis rails, gravity, and a 100 kN tank load distributed to supports). Key performance indicators included maximum/average total deformation, maximum principal stress, factor of safety (FoS), frame mass, and indicative material cost. Mild steel achieved the lowest deformation (12.81 mm; average 0.186 mm) and a FoS of 6.28; SS 304 was comparable in deformation (13.295 mm; average 0.193 mm) with FoS 5.23. Aluminum 7075-T6 showed higher elastic deformation (36.185 mm; average 0.523 mm) but delivered the highest FoS (7.16) and a 62% mass reduction (300 kg vs 790 kg for SS). Maximum principal stresses were nearly identical across materials (~28.65 MPa), remaining well below their respective yields (SS 304 ~292 MPa; IS 2062 ~460 MPa; Al 7075-T6 ~500–540 MPa). Indicative material costs (₹/kg) favored mild steel (60–80) over stainless steel (150–200) and aluminum (400–500). The results quantify clear trade-offs: mild steel offers cost-optimal stiffness; aluminum provides transformative mass savings and safety margin; stainless steel suits higher-corrosion contexts with a weight penalty. These findings support material selection pathways aligned to fleet priorities (capex vs payload/efficiency) and motivate follow-on fatigue/dynamic analyses for duty-cycle certification.